DETERMINAN PENGETAHUAN KESEHATAN REPRODUKSI PADA REMAJA DI SMK GITA KIRTTI 1 JAKARTA TAHUN 2023 - Chusnul Khotimah, (2023)
National survey data show that adolescents have insufficient knowledge about reproductive health. Knowledge of reproductive health is important to avoid reproductive health problems. The purpose of this study was to seek the determinants of reproductive health knowledge in adolescents. This is a cross-sectional study conducted from March to June 2023 to 89 adolescent at SMK Gita Kirtti 1 Jakarta. The instrument was a questionnaire that was filled out via the google form, with data analysis using the Chi-square test and multiple logistic regression tests. The results showed that there was a relationship between gender (p-value = 0,010 (POR = 3,529, 95%CI = 1,433 - 8,691) and the role of peers (p-value = 0,019 (POR = 3,307, 95%CI = 1,305 - 8,379) with knowledge of reproductive health in adolescents. Multivariate analysis found that the sex was the most dominant variable affecting reproductive health knowledge in adolescents POR = 7.347 (95%CI = 2,287 - 23,603). The conclusion of this study is that respondents have less knowledge of reproductive health, with two variables that influence reproductive health knowledge, sex and peers, while sex is a factor that influence the most. It is hoped that there will be collaboration between schools and external parties to be able to provide reproductive health education to both parents and adolescents.